CRUDE EROTISM IN ADVERTISING: analysis of the Calvin Klein brand - Oliveira, Thainá Beatriz; Del Vechio , Gustavo (Revista Interface Tecnológica, 2022)
Body care, that is, physical shape, beauty, health and well-being are increasingly evident among young people, adults and the elderly. For this reason, many brands explore sensuality in their advertisements, in an attempt to draw attention to the images and products they present. Put that way, this study seeks to assess whether images with sexual connotations help brands gain more visibility. For this, after building the theoretical foundation, the study evaluates a specific brand, Calvin Klein, which for several decades has explored sensuality in its campaigns, making this characteristic part of its identity. What can be seen from the study is that sensuality can draw attention and actually influence purchase decisions; however, it is necessary to be careful with exaggerations, as bad choices can generate controversy and criticism from the public, something that may not be beneficial for the brands involved.
Keywords: Brand image; Communication; Advertising; Sensuality; Nudity